2010
DOI: 10.2353/ajpath.2010.091279
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Stimulation Triggers Crescentic Glomerulonephritis by Multiple Mechanisms Including a Direct Effect on Renal Cells

Abstract: A role for toll-like receptor 4 (TLR4) has been suggested in previous studies of glomerulonephritis, but the complex integration of these effects has not been explored. To separate effects on the innate and adaptive immune responses, we use the autologous nephrotoxic nephritis model with two disease induction protocols. First, we give a TLR4 ligand at the time of immunization and show the effects are mediated via TLR4 by comparing wild-type and TLR4-deficient mice. In wild-type mice histological measures of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…More recently it has been shown that exogenously administered agonists of TLR3, TLR7 and TLR9 can exacerbate murine lupus [1], [2], [3], [4]. In addition several studies using the nephrotoxic nephritis model have shown a role for TLR2 and TLR4 through a number of mechanisms [5], [6], [7], [8]. Together these data support the idea that TLRs play a role in the exacerbation of lupus by bacterial and viral infection, as can be observed clinically.…”
Section: Introductionsupporting
confidence: 59%
“…More recently it has been shown that exogenously administered agonists of TLR3, TLR7 and TLR9 can exacerbate murine lupus [1], [2], [3], [4]. In addition several studies using the nephrotoxic nephritis model have shown a role for TLR2 and TLR4 through a number of mechanisms [5], [6], [7], [8]. Together these data support the idea that TLRs play a role in the exacerbation of lupus by bacterial and viral infection, as can be observed clinically.…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, TLR4 expression in intrinsic renal cells and leukocytes has been reported to contribute to various acute and chronic kidney diseases. [27][28][29][30][31] The role of TLR4 in the pathogenesis of DN has been increasingly recognized. We and others have shown that TLR4 mediated high glucose-induced tubular inflammation, 19,32 and that the endogenous TLR4 ligand HMGB1 may have a role in TLR4 activation in DN.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies have focused on the phase of acute glomerular injury (which may be associated with impaired renal function in association with crescentic disease), while data on long-term follow-up to determine if the mice develop progressive tubulointerstitial fibrosis, tubular atrophy and renal insufficiency are sparse. Some studies have reported interstitial inflammation [59–61] and elevated serum creatinine levels but the latter are likely a consequence of severe glomerular damage [62, 63]. Our preliminary studies with NTS generated by the Shankland laboratory suggest that progressive tubulointerstitial disease requires repeated NTS injections [64].…”
Section: Alternative Mouse Ckd Modelsmentioning
confidence: 99%